The Role of People's Business Credit (Kur) and The Use of E-Marketing For The Development of Msmes In Medan Deli District In Medan City - Sujinny, Sujinny; Loo, Petrus; Nasution, Lisa Elianti (Dinasti Publisher, 2024)
This research aims to find out whether People's Business Credit has an effect on the development of MSMEs in Medan Deli subdistrict in Medan City, to find out whether E-Marketing has an effect on the development of MSMEs in Medan Deli subdistrict in Medan City, and to find out whether People's Business Credit and E-Marketing have an effect on development of MSMEs in Medan Deli sub-district in Medan City. The type of data for this research is quantitative data. Data analysis techniques in this research are validity test, reliability test, descriptive statistics, classic assumption test (normality test, multicollinearity test, heteroscedasticity test), multiple linear regression analysis, hypothesis testing (t test, f test), and coefficient of determination. The results of this research state that the influence of people's business credit and e-marketing on the development of MSMEs in Medan Deli subdistrict in Medan City is shown by the results of multiple linear regression analysis which means that the variables of people's business credit and e-marketing together have an influence on the development of MSMEs in Medan district. Deli in Medan City.